Operative Strategies for Perforated Diverticulitis: A Systematic Review and Meta-analysis. Issue 12 (December 2018) - Acuna, Sergio A.; Wood, Trevor; Chesney, Tyler R.; Dossa, Fahima; Wexner, Steven D.; Quereshy, Fayez A.; Chadi, Sami A.; Baxter, Nancy N.
Abstract : BACKGROUND: The traditional approach for perforated diverticulitis, the Hartmann procedure, has considerable morbidity and the challenge of stoma reversal. Alternative procedures, including primary resection and anastomosis and laparoscopic lavage, have been proposed but remain controversial. OBJECTIVE: The purpose of this study was to compare operative strategies for perforated diverticulitis. DATA SOURCES: MEDLINE, Embase, Cochrane Library, and the grey literature were searched from inception to October 2017. STUDY SELECTION: We included randomized clinical trials evaluating operative strategies for perforated diverticulitis. INTERVENTIONS: Hartmann procedure, primary resection and anastomosis, and laparoscopic lavage were included. MAIN OUTCOME MEASURES: Data were independently extracted by 2 investigators. Risk of bias was evaluated using the Cochrane risk-of-bias tool. Pooled risk ratios for major complications, reoperation, and mortality were determined using random-effects models. RESULTS: Six trials including 626 patients with perforated diverticulitis were identified. Laparoscopic lavage and sigmoidectomy had comparable rates of early reoperation and postoperative mortality; major complications (Clavien–Dindo >IIIa) were more frequent after laparoscopic lavage (RR = 1.68 (95% CI, 1.10–2.56); 3 trials, 305 patients). Comparing approaches for sigmoidectomy, primary resection and anastomosis had similar rates of major complications (RR = 0.88 (95% CI, 0.49–1.55); 3 trials, 255 patients) and postoperative mortality (RR = 0.58 (95% CI, 0.20–1.70); 3 trials, 254 patients) compared with the Hartmann procedure. However, patients who underwent primary resection and anastomosis were more likely to be stoma free at 12 months compared with the Hartmann procedure (RR = 1.40 (95% CI, 1.18–1.67); 4 trials, 283 patients) and to experience fewer major complications related to the stoma reversal procedure (RR = 0.26 (95% CI, 0.07–0.89); 4 trials, 186 patients). LIMITATIONS: There were no limitations to this study. CONCLUSIONS: Laparoscopic lavage is associated with increased risk of major complications versus primary resection for Hinchey III diverticulitis. The lower rate of stoma reversal and higher rate of complications after the Hartmann procedure suggest primary resection and anastomosis as the optimal management of perforated diverticulitis. Abstract : Supplemental Digital Content is available in the text.